Locker room talk - McNair, Gary (Oberon modern plays., 2017)
"'Grab them by the pussy!' Donald J Trump, 45th President of the United States. Locker Room Talk is a provocative piece of event theatre. Inspired by Trump's leaked sexually aggressive comments, the show is a confronting exploration of the phenomenon the then-presidential candidate later dismissed as 'locker room talk'. Does Trump speak to a silent majority or is he simply a loathsome individual? To find out, Gary McNair had frank and honest conversations with men in private about women. The words of these men are performed by a cast of women in this verbatim piece."--Page 4 of cover.